Pre-Olympic ice-skaters training versus muscle fatigability assessed by sEMG - Pakosz, P.; Lukanova-Jakubowska, A.; Konieczny, M. (Preprints, 2019)
The aim of this study was to investigate the size of the change in fatigability of gluteus maximus muscles during difficult endurance training in dynamic conditions. The research covered involved eight female athletes of the Polish National Team in short track, which had been prepared to the Olympic Games in PyeongChang. The sEMG system was used to measure fatigue of right and left gluteus maximus muscles, in the modified Biering-Sorensen test. The test was conducted five times during the training: before training, after warmup, and after each of 3 series of the endurance training. Comparing the mean frequency of the surface electromyography power spectrum of the first and the last seconds of the test, statistically significant reduction (p<0.05) of the average frequency value of the right muscle from 55.61±7.08 Hz to 48.64±4.48 Hz and left muscle from 58.78±4.98 Hz to 53.18±4.62 Hz was reported. In the conducted Biering-Sorensen test, the value of the muscle signal frequency measured by surface electromyography decreases, which may prove the muscle fatigue. Reductions in the frequency measured in the first and the last second of the test, was higher of the right lower limb. The size of the d Cohen effect in fatigue drops along with subsequent five tests during the training.